Evaluasi Fungsional Dan Estetika Pohon Pada Lanskap Jalan Uluwatu I, Jimbaran - Paramita, Gusti Ayu Diah Arya; Krisnandika, Anak Agung Keswari; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol.9, No.1, April 2023, 2023)
Functional and Aesthetic Evaluation of Trees in the Road Landscape of Uluwatu I, Jimbaran Street . Uluwatu I, Jimbaran street must have a road landscape that can provide comfort and create high beauty for road users to support tourism infrastructure on Uluwatu I, Jimbaran street. Therefore, this study aims to evaluate the functional and aesthetic value of road landscape trees. The method used is the observation method. There are two aspects of tree function that are assessed, namely the shade function and the pollution control function. In the assessment of all aspects of tree function, segment 2 received the highest percentage of assessment (64.6%). Each function has an average fulfillment of 54.1% for the shading function and 51.5% for the pollution control function, which is included in the medium category. For aesthetic value, in landscape photos of similar tree groups there are only two landscape photos that fall into the category of high aesthetic value, namely landscape photos 3 (segment 1) and landscape photos 7 (segment 4). In the mixed tree group landscape photo, there is only one landscape photo that is included in the high aesthetic value category, namely landscape photo 8 (segment 4). Therefore, intensive care is needed for young trees, so that tree height, branch height above the ground and maximum canopy shape can reach the ideal value. Adding a layer of plants, also adding tree planting to create a road landscape with high functional and aesthetic value.